Estrutura populacional de jaboticabeiras no sudoeste do Paraná - Moura, Amanda Pacheco Cardoso (2017)
In the Brazilian state of Paraná were identified 14 forest fragments of Mixed Ombrophilous Forest where species Plinia cauliflora occurs. Most of those populations are in a legal reserve area and suffer from extractive harvesting of fruits (jaboticabas) and other anthropogenic actions. Our objective with this work was to determine ontogenetic stages, regeneration and spatial distribution on populations of jaboticabeira (Plinia cauliflora) in the Southwest of Paraná. We determine the ontogenetic stages by random sampling (n=50). We set sample units (70x70m) in six fragments located in four cities in the southwest of Paraná. On those fragments we collected diameter, height and Cartesian coordinates (x, y). Collected data were evaluated through descriptive statistics. Spatial distribution and spatial dependence were verified through the univariate and bivariate O'ring function. We found five ontogenetic stages for jaboticabeira: seedlings (h ≤ 0.10 m); juveniles (h> 0.10 m to 1.70 m); immature (height> 1.70 m to 5 m); virgin (h> 5 m, without reproductive structures); reproductive (h> 5 m with reproductive structures). Results showed that there are structural differences between the remnants which have on effect on potential regeneration of the populations. The populations of Clevelândia, Pato Branco I and II have all ontogenetic classes established. They also, showed a greater individuals numbers of classes which represent regeneration (seedlings, juveniles and immature) as well J-inverted height and diameter distribution. On the other half of populations the opposite situation was noticed. We attributed these results basically by the use of areas historically and consequently greater chances of possible existence dispersing animals which increases chances of germination and establishment of jaboticabeira seedlings. Spatial distribution varied between populations showing a random distribution on most ontogenetic stages exceptionally for Clevelândia and Chopinzinho II populations. There was no spatial dependence between ontogenetic pairs of stages in any population. These results may be attributed to dispersion or other factors which requires further studies. We accomplished that management history of the areas combined with, a continuous anthropic action in some places, seems to be one of the main obstacles in the regeneration of jaboticabeira individuals and consequent recruitment in larger size classes.